2011
DOI: 10.1177/0278364911408155
|View full text |Cite
|
Sign up to set email alerts
|

Learning spatial relationships between objects

Abstract: Although a manipulator must interact with objects in terms of their full complexity, it is the qualitative structure of the objects in an environment and the relationships between them which define the composition of that environment, and allow for the construction of efficient plans to enable the completion of various elaborate tasks. In this paper we present an algorithm which redescribes a scene in terms of a layered representation, from labeled point clouds of the objects in the scene. The representation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 20 publications
1
59
0
Order By: Relevance
“…This corresponds to the minimum and maximum range of all possible combinatorial motions of 3. There have been many works trying to find joint positions as part of kinematic structure estimation [13], [14], [15], [71]. Yan and Pollefeys [13] estimate joint positions as the intersection of two motion subspaces, but their method is vulnerable to noise.…”
Section: Third Order Similarity: Combinatorial Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to the minimum and maximum range of all possible combinatorial motions of 3. There have been many works trying to find joint positions as part of kinematic structure estimation [13], [14], [15], [71]. Yan and Pollefeys [13] estimate joint positions as the intersection of two motion subspaces, but their method is vulnerable to noise.…”
Section: Third Order Similarity: Combinatorial Motionmentioning
confidence: 99%
“…The estimate in [14] is based on probabilistic inference which can find the number of joints and their connections adaptively, but the method is sensitive to the prior and has difficulty in recovering from a poor initialisation. In [71] a SVM based method which is conceptually similar to our proposal is presented, but ours is simpler than theirs. We tested these methods, and have found that their joint estimates are similar or worse compared to ours.…”
Section: Third Order Similarity: Combinatorial Motionmentioning
confidence: 99%
“…Rosman and Ramamoorthy [25] present a method for learning spatial relationships between objects using the segmented point clouds. In their work the lack of information about the complete set of objects and physical interactions between objects are not considered.…”
Section: Related Workmentioning
confidence: 99%
“…Rosman and Ramamoorthy [21] proposed the use of a contact network to learn the spatial relations between objects. Contact points were detected using a support vector machine to separate the point clouds of the objects.…”
Section: A Related Workmentioning
confidence: 99%